Air-duct pressure balancing design & experiment - Lwin, Ei Wah (2015)
Balancing in a duct system is maintaining the air flow and pressure in the duct to a design flow. It is an experiment of measuring the air flow and adjusting the dampers in order to get specified airflow. As calculation approaches are not accurate enough, software simulations are used to balance the system. In this experiment, the balancing of the duct will be done by a computer program. Firstly, the flow and pressures of the system are measured, and then followed by the damper adjustments. The flows and adjustments process are done repeatedly so as to achieve the designed flow. Without the simulation, the adjustment calculations for each damper may take a lot of time and less accurate. By using software simulation, the angle prediction for the dampers can be done faster. After the simulation, measurements will be done with reference to the results obtained. This can makes the process much faster and less expensive at the same time.